Daily life of patients with chronic renal failure receiving hemodialysis treatment El día a día de personas con insuficiencia renal crónica en tratamiento de hemodiálisis O cotidiano de pessoas com insuficiência renal crônica em tratamento hemodialítico - Karina Viviani Bezerra; Jair Lício Ferreira Santos (Universidade de São Paulo, 2008)
This analytical descriptive study aimed at assessing the perception of people with chronic renal failure in relation to their daily and occupational activities. The sample was formed by 35 men and 35 women receiving hemodialysis treatment with ages between 17 and 60 years. The instrument used was the SAOF (Self Assessment of Occupational Functioning). The data were submitted to statistical analysis and the areas with greater choice of the alternative "need to improve" were habits (20%) and values (20.5%). In these areas, the proportion related with difficulties was more evident regarding organization of the daily life, the changes of routines and the expectations about the future. Therefore, occupational therapy, as it presents instrumental resources to reorganize daily life of these patients, can contribute for their care as well as with information for nursing. Este estudio analítico-descriptivo tiene como objetivo evaluar la percepción de las personas con insuficiencia renal crónica en relación con las actividades cotidianas y ocupacionales. El análisis fue compuesto por 35 hombres y 35 mujeres en tratamiento de hemodiálisis con edad entre 17 y 60 años. El cuestionario utilizado fue el SAOF (Self Asesment of Occupational Functioning). Los datos fueron sometidos a análisis estadístico y las opciones que fueron las más escogidas en la alternativa "necesidad de mejorar" fueron la de hábitos (20%) y valores (20,5%). En esas áreas la proporción relacionada a las dificultades fue más evidente en lo que se refiere a la organización de lo cotidiano, a cambios de rutinas y las expectativas sobre el futuro. Por lo tanto, la terapia ocupacional, por presentar recursos instrumentales para la reestructuración de lo cotidiano de esos pacientes, puede contribuir para asistirlos, así como entregar informaciones importantes para la enfermería. Este estudo analítico-descritivo objetivou avaliar a percepção das pessoas com insuficiência renal crônica em relação às atividades cotidianas e ocupacionais. A análise foi composta por 35 homens e 35 mulheres em tratamento hemodialítico com idade entre 17 e 60 anos. O questionário utilizado foi o SAOF (Self Assesment of Occupational Functioning). Os dados foram submetidos à análise estatística e as áreas com maior escolha da alternativa "necessidade de melhora" foram de hábitos (20%) e valores (20,5%). Nessas áreas, a proporção relacionada às dificuldades foi mais evidente no que se refere à organização do cotidiano, a mudanças de rotinas e às expectativas quanto ao futuro. Portanto, a terapia ocupacional, por apresentar recursos instrumentais para a reestruturação do cotidiano desses pacientes, pode contribuir para a assistência deles assim como informações para a enfermagem.